PENGHEMAT BAHAN BAKAR PADA KOMPOR GAS RUMAH TANGGA - Abdurrachim, Abdurrachim; Wardani, D; Yudi, T (Mesin, 2009)
A gas saver for gas cooking stove has been investigated, designed, and tested in this work. The device is a conical vertical cylinder placed around the cooking pan. The application of the device does not need any modification of the cooking stove nor the cooking pan. The temperature distribution of hot gas around the cooking pan is computed by means of numerical method. It is found that a significant fuel saving can be obtained using the gas saver because the vertical wall becomes an energy input area to the cooking pan which is not the case in absence of the gas saver. The tests of gas saver have been carried out using aluminum cooking pans of 16 cm and 29 cm diameters to heat 1.30 kg and 2.35 kg of water, respectively. In this preliminary test the gas saver is made of aluminum laminated cartoon. It is found that the gas saver reduces the cooking time and reduces the fuel consumption about 9 â 11 %. With the assumption of LPG consumption 12 kg/stove/ month,, 6,000,000 cooking stove used (government plan) and 10% of fuel saving, 86,400,000 kg of LPG will be saved per year. With the price of a gas saver Rp 20,000.00/piece/year, the total money saved will be amounted to Rp 240,000,000.00 per year.